A new species of the extinct mid-Cretaceous genus Scydmobisetia Jałoszyński & Yamamoto (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Bai, Ming; Wang, Bo (Zootaxa, 2020)
The extinct genus Scydmobisetia Jałoszyński & Yamamoto comprises three species known from inclusions in the mid-Cretaceous Myanmar amber. Another species, Scydmobisetia dentipes Jałoszyński & Bai sp. n. is described from the same source. The holotype is a male showing a unique sub-basal tooth-like projection on the profemur.